Visible-Light-Promoted Synthesis of Vinyloxaziridines from Conjugated Carbonyls - Austin, Brooke E.; Palner, Ryan P.; Tobias, Elissa M.; Madiu, Rufai; Doran, Erin L.; Doran, Jenna M.; Howard, Amari M.; Stroud, James L.; Rossi, Morgan E.; Moskovitz, Dylan A.; Rivera, Dominic A.; Mullen, Michael D.; Zinsky, Amy H.; Rosario, Rose A.; Moura-Letts, Gustavo (Synlett, 2023)
We report the first visible-light-promoted synthesis of vinyloxaziridines from simple conjugated nitrones. We have found that vinyl nitrones formed by the condensation reaction between conjugated carbonyls and hydroxylamines undergo visible-light-promoted energy-transfer isomerization to the respective vinyloxaziridines in very high yields and selectivities. The reaction scope expands to a large array of substitution patterns, and evidence indicates that the proposed energy-transfer pathway is the predominant mechanism for this transformation.
Keywords: photoisomerization; oxaziridines; nitrones; visible light; single-electron transfer